2022
DOI: 10.1111/clr.13961
|View full text |Cite
|
Sign up to set email alerts
|

Does machine‐vision‐assisted dynamic navigation improve the accuracy of digitally planned prosthetically guided immediate implant placement? A randomized controlled trial

Abstract: Immediate implant placement has received increasing attention due to the shortened treatment period and predictable prognosis, which has the potential to improve patient satisfaction (Kan et al., 2018;Shi et al., 2015). Placement, however, utilizes mainly the socket and the alveolar bone plate slope; bleeding from the socket interferes with proper visualization of the implant site, thus making the surgery more difficult and affecting the accuracy of implant placement (Blanco, Carral, Argibay, & Liñares, 2019).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
1
34
1
Order By: Relevance
“…When the levels indicated by the K-means classification are applied as thresholds in the currently available literature on CAIS, the combination of static and navigation CAIS as applied in this study produced the smallest average deviation reported so far (Aydemir & Arısan, 2020;Block et al, 2017;Kaewsiri et al, 2019;Smitkarn et al, 2019;Sun et al, 2020;Tahmaseb et al, 2018;Wei et al, 2022;Wu et al, 2020;Yimarj et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…When the levels indicated by the K-means classification are applied as thresholds in the currently available literature on CAIS, the combination of static and navigation CAIS as applied in this study produced the smallest average deviation reported so far (Aydemir & Arısan, 2020;Block et al, 2017;Kaewsiri et al, 2019;Smitkarn et al, 2019;Sun et al, 2020;Tahmaseb et al, 2018;Wei et al, 2022;Wu et al, 2020;Yimarj et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Thereafter, static CAIS utilizes a surgical guide 3D printing in resin to transfer the virtually planned implant position to the surgical field, while dynamic CAIS systems utilize dynamic navigation, where the actual position of the drill is projected on the patient's radiographic anatomy in real time on a screen. Both static and dynamic CAIS systems have been assessed in multiple clinical scenarios from a single implant to fully edentulous patients with comparable outcomes in terms of accuracy and precision (Jaemsuwan et al, 2022; Kaewsiri et al, 2019; Smitkarn et al, 2019; Wei et al, 2022; Yimarj et al, 2020). Although both techniques can significantly reduce deviation when compared with freehand placement (Tahmaseb et al, 2014), they too suffer from different limitations and sources of error.…”
Section: Introductionmentioning
confidence: 99%
“…CAIS system nowadays typically contains static and dynamic technological pathways [ 18 ]. Clinical evidence has proved that both systems have currently achieved significantly higher accuracy of implant placement than the freehand protocol [ 6 , 7 , 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these in vitro studies were conducted in cadavers providing better visual field and operation access and being absent for intraoral patient conditions. Shimin Wei et al reported that the global deviation at entry and apex was 1.01 mm and 0.88 mm in the immediate implant placement using dynamic CAIS protocol [ 7 ]. However, there were only 12 patients involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation